The battery charging station location problem: Impact of users’ range anxiety and distance convenience - Guo, Fang; Yang, Jun; Lu, Jianyi (Transportation research. Part E, Logistics and transportation review, 2018)
•We build a BCS location model as a leader-follower game.•The heuristic algorithm is proposed to solve this problem.•We conduct parameter analysis of flow decay function and distance deviations.•We conduct parametric analysis on the real-world road network. Key to the mass adoption of electric vehicles (EV) is establishing a sufficient recharging infrastructure network, based on customer behavior and psychology. This study examines the battery charging station location problem, considering users’ range anxiety and distance deviations, two major barriers to the mass adoption of EV. The problem is formulated as a bi-level integer programming model based on a range anxiety function. Then, the problem is solved using an adaptive large-neighborhood search, combined with a k-shortest path algorithm and an iterative greedy heuristic. Finally, the effects of parameters are analyzed in the context of a real-world road network.